Spiritual care in nursing: an overview of the measures used to assess spiritual care provision and related factors amongst nurses - Harrad, Rachel; Cosentino, Chiara; Keasley, Robert; Sulla, Francesco (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Spiritual wellbeing has important implications for an individual’s health and wellbeing. Whilst the provision of spiritual care and assessment of spiritual needs is a vital part of the nurse’s role, literature suggests that nurses do not always engage in spiritual care with their patients or assess their spiritual needs. This review aims to ascertain wider reasons for this inconsistent spiritual care delivery by nurses to their patients. Methods: A review of the literature was conducted to identify instruments available relating to nursing professionals spiritual care and assessment. Results: 14 measures relating to spiritual care and assessment were identified covering the key domains of: ‘Beliefs and values and attitudes around spiritual care,’ ‘Frequency of provision or extent to which they provide spiritual care or willingness,’ ‘Respondents’ level of knowledge around spirituality and spiritual care,’ ‘Ability to respond to spiritual pain,’ and ‘Multiple Domains: beliefs and attitudes around spirituality and spiritual care, amount of preparation, training and knowledge, spiritual care practices, perceived ability and comfort with provision and perceived barriers to provision.’ Conclusions: A lack of standardisation in the conceptualisation and assessment of spiritual care causes challenges in reviewing, however several themes do emerge. In general student and qualified nurses are aware of the importance of providing spiritual care and are hindered by a lack of education about how best to implement such care. The religiosity of individual nurses or their training institutions seems to be of less importance than training in spiritual care interventions.